Callogobius winterbottomi, a new species of goby (Teleostei: Gobiidae) from the Western Indian Ocean - Delventhal, Naomi R.; Mooi, Randall D. (Zootaxa, 2013)
Callogobius winterbottomi new species is described from the 33.8 mm SL holotype and two paratypes (32.2 mm SL and 22.9 mm SL) from the Comoros, Western Indian Ocean. It is distinguished from all other known Callogobius species by the following combination of characters: sensory pores absent, 23–26 scales in lateral series, and sensory papillae pre-opercular row not continuous with transverse opercular row. One additional specimen of Callogobius winterbottomi was located from South Africa. A new standardized naming system for Callogobius sensory papillae rows is presented for identification and clarification of character states among Callogobius species. The new species is tentatively placed among what we term the “sclateri group”, a clade including C. sclateri (Steindachner) and three other species that exhibit a modified female urogenital papilla with lateral distal flaps and elongate ctenii on the caudal peduncle scales. Callogobius tutuilae (Jordan & Seale) is removed from synonymy with C. sclateri because it has partially united pelvic fins (vs separate) and the preopercular sensory papillae row is continuous with the transverse opercular row (vs separate).